1970
DOI: 10.1139/m70-218
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase localization and spheroplast formation of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa cells grown in the presence of low levels of inorganic phosphate contain an inducible alkaline phosphatase system. The enzyme has been localized by electron microscopic techniques in the region between the cytoplasmic membrane and the tripartite layer of the cell wall, i.e. the periplasmic space. No deposits of lead salts are observed upon examination of either uninduced cells or cells in which the enzyme has been completely removed by 0.2 M magnesium washing. Samples of cells which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…Myxospore breakage was monitored by phase-contrast microscopy. Samples were then centrifuged at 5,000 x g for 5 min to remove debris from the cell extract, and supernatants (0.3-ml samples) were assayed for alkaline phosphatase (4). For determination of the alkaline phosphatase activity during starvation-induced cell development, exponential-phase cells were concentrated by centrifugation, suspended in CF broth to 3,000 or 4,500 Klett units, and incubated at 30°C or heat shocked, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Myxospore breakage was monitored by phase-contrast microscopy. Samples were then centrifuged at 5,000 x g for 5 min to remove debris from the cell extract, and supernatants (0.3-ml samples) were assayed for alkaline phosphatase (4). For determination of the alkaline phosphatase activity during starvation-induced cell development, exponential-phase cells were concentrated by centrifugation, suspended in CF broth to 3,000 or 4,500 Klett units, and incubated at 30°C or heat shocked, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures described by Nelson et al (22) were used to obtain the periplasmic, cytoplasmic, and membrane fractions of M. xanthus cells. The fractions were checked for cross contamination by assaying each for specific enzyme markers: alkaline phosphatase (periplasmic [5]), succinic dehydrogenase (membrane [17]), and glutamic dehydrogenase (cytoplasmic [7]). All fractions showed less than 10% cross contamination.…”
Section: Methodsmentioning
confidence: 99%
“…In previous papers (3)(4)(5) we reported that all of the cell-bound alkaline phosphatase is removed from P. aeruginosa by 0.2 M Mg2+. In the present study we have shown that the LPS (23).…”
Section: Discussionmentioning
confidence: 90%
“…The LPS was hydrolyzed in 0.02 N H2SO4 in a boiling water bath as described by Osborn et al (22). The KDO was determined by the thiobarbituric acid procedure of Weissbach (37) (4,5). Magnesiumlysozyme spheroplasts were prepared similarly, except that the 20% sucrose was replaced by 0.2 M MgCl2 and 0.01 M Tris (pH 8.4).…”
mentioning
confidence: 99%